Automated Smart Garden using IoT System - Ramu, Hemaraj; Che Soh, Mohd Jais (Evolution in Electrical and Electronic Engineering, 2024)
This study is an innovative and original work that combines IoT technology with automation to revolutionize traditional gardening practices. This work aims to improve plant health and promote effective growth while also enabling users to remotely monitor the health of their indoor plants and the environment. The work reduces the need for human involvement and develops a fully automated solution using sensors, micro-controllers, and IoT technology by implementing a system that makes use of temperature sensors to effectively control the plant environment. Complete circuit design simulations and code development are part of the methodology, which has resulted in significant advancements. The IoT platform has been successfully developed, making it possible for data to be smoothly retrieved from the Wi-Fi module and displayed on the IoT portal server. Both the serial monitors and the IoT server portal accurately record and display crucial measurements like humidity, temperature, and soil moisture content. With improved plant care and higher user convenience, the Automated Smart Garden using IoT System introduces an innovative approach to transform gardening methods.